If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x+3)=7x-2x+11
We move all terms to the left:
9(x+3)-(7x-2x+11)=0
We add all the numbers together, and all the variables
9(x+3)-(5x+11)=0
We multiply parentheses
9x-(5x+11)+27=0
We get rid of parentheses
9x-5x-11+27=0
We add all the numbers together, and all the variables
4x+16=0
We move all terms containing x to the left, all other terms to the right
4x=-16
x=-16/4
x=-4
| (3k+9)(k-7)=0 | | 4x-6-8=4+2x | | 7(h=3)=6(h-3) | | 10-2(x+3)=10(x+4)-15 | | 1/2(x+1)+3/4(x+4)=x+5 | | 5-3920x^-2=0 | | 9-4c=17 | | 11x+1=9x+17 | | 11x+1=9x+5 | | |3x-1|=|2x+3| | | (3n+21)+(2n+39)=180 | | 1/2(x+1)+3(x+4)=x+5 | | -12x+2(4x-3)=-14-3x | | 2(x+3)+5x=x+20 | | 10x+2=4x+8=13x+3 | | (x-2)^2+17=18 | | 2/5(8x+7)+1/15(4x-9)=1/25(24x+11)+4/3(2x+3)-2 | | 12=g/6 | | 7y-2=4y+13 | | $385/k=$5 | | -y/7=48 | | 8a+3=2(3a+1) | | m-62.5=-6.3 | | 2x^2-8x-10x=2 | | 14x+10=3x+3 | | 2(x+2)+4=8 | | x/3-8=30 | | p-7/18=11/12 | | X^2+x-3x-15=0 | | 12x-6+36=5x+7 | | -5y+5=-6y+9 | | -10+7(8-6b)=10-6(12b+9) |